Validation and Reliability of Hidden Informal Curriculum Assessment Tool In Pakistani Preceptive - Hanif, Faisal; Khan, Rehan Ahmed; Yasmeen, Rahila (Pakistan Armed Forces Medical Journal, 2025)
Objective: To establish construct validity of the Hidden Informal Curriculum Assessment Tool(HICAT) among Pakistani medical students. Study Design: Quantitative Instrument validation study Place and Duration of Study: Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan from Jan to Jun 2023. Methodology: Data collection for was done using manually printed forms, with a minimum of thirty participants per session. A total of 271 participants were involved. The first phase of the study involved response process validity, Six individuals—four medical students and two teachers—reviewed the HICAT tool. feedback on clarity, relevance, and comprehensibility of the items was obtained. A mix of verbal probing and think-aloud techniques was used to assess content validity. The tool was revised to reduce bias by mixing positive and negative items. The participants rated the items on a five-point scale.The second phase focused on data collection from 3rd, 4th, and 5th-year students. After the collection of data, analysis was done by doing a Confirmatory factor analysis. Results: After rerunning confirmatory factor analysis, items that had low loading in each component were removed, and modification indices were established to obtain a goodness-of-fit model. In summary, the construct validity analysis of the HICAT tool resulted in the removal of one item from positive traits and three items from negative traits, leaving a total of sixteen items. Conclusion: The HICAT tool demonstrates satisfactory construct validity in the Pakistani culture and context for assessing the hidden informal curriculum among medical educational institutions.